Islam dalam Jagad Pikir Melayu - Junaidi, Junaidi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2014)
AbstrakAgama dan kebudayaan merupakan bagian penting dalam kehidupan manusia. Adakalanya agama dipengaruhi kebudayaan atau sebaliknya kebudayaan yang dipengaruhi agama. Masuknya Islam ke tanah Melayu memberikan pengaruh terhadap corak kebudayaan dan pemikiran Melayu. Penelitian ini bertujuan untuk mengkaji nilai-nilai Islam yang terdapat dalam teks Tunjuk Ajar Melayu dengan menggunakan pendekatan strukturalis. Hasil penelitian menunjukkan bahwa dalam Tunjuk Ajar Melayu terdapat nasihat, pesan, pikiran dan gagasan untuk memegang teguh Islam dalam kehidupan orang Melayu. Dalam Tunjuk Ajar Melayu diungkapkan posisi adat dan syarak, Islam sebagai identitas orang Melayu, anjuran bertakwa kepada Allah, Islam untuk pembentukkan karakter anak dan persiapan menuju akhirat. Penelitian ini menyimpulkan bahwa Islam sangat berpengaruh dalam pembentukan pemikiran Melayu sehingga Islam dianggap sebagai identitas utama orang Melayu. —AbstractReligion and culture are important in human life. Sometimes, a religion is influenced by culture or in any case culture is influenced by religion. The coming of Islam to Malay land influenced on the characteristic of Malay culture and minds. This research aims to analyze the Islamic values on text of “Tunjuk Ajar Melayu” by using structuralis approach. Findings of research show that “Tunjuk Ajar Melayu” consist of advices, messages, thoughs, and ideas to keep Islam in the life of Malay people. It expresses the position of “adat” and “syarak”, Islam as identity of Malay people, messages of devoting to Allah, Islam to build the children character and preparation toward hereafter. This research concludes Islam greatly influences in building Malay culture and minds, and therefore Islam is regarded as main identity for Malay people.